Tissue-specific transcriptome profiling of the citrus fruit epidermis and subepidermis using laser capture microdissection - Matas, Antonio J. (Oxford University Press, 2010)
Most studies of the biochemical and regulatory pathways that are associated with, and control, fruit expansion and ripening are based on homogenized bulk tissues, and do not take into consideration the multiplicity of different cell types from which the analytes, be they transcripts, proteins or metabolites, are extracted. Consequently, potentially valuable spatial information is lost and the lower abundance cellular components that are expressed only in certain cell types can be diluted below the level of detection. In this study, laser microdissection (LMD) was used to isolate epidermal and subepidermal cells from green, expanding Citrus clementina fruit and their transcriptomes were compared using a 20k citrus cDNA microarray and quantitative real-time PCR. The results show striking differences in gene expression profiles between the two cell types, revealing specific metabolic pathways that can be related to their respective organelle composition and cell wall specialization. Microscopy provided additional evidence of tissue specialization that could be associated with the transcript profiles with distinct differences in organelle and metabolite accumulation. Subepidermis predominant genes are primarily involved in photosynthesis- and energy-related processes, as well as cell wall biosynthesis and restructuring. By contrast, the most epidermis predominant genes are related to the biosynthesis of the cuticle, flavonoids, and defence responses. Furthermore, the epidermis transcript profile showed a high proportion of genes with no known function, supporting the original hypothesis that analysis at the tissue/cell specific levels can promote gene discovery and lead to a better understanding of the specialized contribution of each tissue to fruit physiology.